Men who suffered Intimate Partner Violence: Impressions about existing public campaigns and recommendations for new ones - Reis, E.; Moleiro, C.; Arriaga, P. (1ª Conferência de Saúde Societal:Saúde societal no futuro Pós-covid -19, 2022)
Over the last decades, the negative effects of intimate partner violence (IPV) directed at men in abusive different-sex and same-sex relationships have been increasingly investigated. Men who suffer IPV face many barriers to help-seeking, and to overcome them, public awareness campaigns have been developed. Women who were targets of IPV have often found campaigns targeting them to be harmful and misleading, and previous research suggests that following the principles of formative research may improve campaigns' effectiveness and reduce unwanted negative effects. This article documents the theory-based formative research conducted with 14 men abused in different-sex and same-sex relationships for the creation of targeted campaigns. Through semistructured interviews, men were asked about their overall knowledge of campaigns, what they thought about specific pictorial IPV campaigns, and their suggestions for the development of new ones. Thematic analysis and a theoretically grounded coding scheme were used to analyze the content of the interviews with high inter-rater reliability. Overall, our results indicate that most men were not aware of campaigns in Portugal, and their impressions about the ones they recalled were mixed. Men praised clear messages informing forms of violence. Nonetheless, some responded negatively to the inclusion of words such as shame” and victim”, as well as the depiction of bruises. According to them, future campaigns targeting men should portray real people” like them and provide information on self-efficacy, efficacy of recommended responses, and threat susceptibility. Our findings mirror previous findings with women who suffered IPV, but also provide theoretically grounded novel contributions. They highlight the importance of considering the population of interest s insights when developing and testing new interventions, which is of added importance for this and other already vulnerable populations in the midst of the COVID-19 pandemic.